Analyzing Religious Hoaxes and Information Literacy: A Qualitative Study of @JabarSaberHoaks - Mochamad Syaefudin; Amelia Dwi Handayani; Handini Handini (Profetik: Jurnal Komunikasi, 2025)
This study aims to explore how religious hoax content is interpreted and how information literacy competencies are articulated through the Instagram account @jabarsaberhoaks. Using a qualitative content analysis approach, this research analyzes seven hoax posts related to religious issues and classifies them according to First Draft’s typology of misinformation and disinformation. The findings reveal that @jabarsaberhoaks adopts a consistent educational approach that clarifies misleading religious information and embeds information literacy elements, such as fact verification, source evaluation, and hoax categorization, within each clarification post. These posts address various hoax types, including fabricated content, imposter content, manipulated content, misleading content, false context, false connection, and satire/parody. The study concludes that @jabarsaberhoaks plays a strategic role in cultivating public critical awareness and promoting digital literacy, especially in the context of religious hoaxes in West Java.